(untitled) (Research, Society and Development, 2021)
The aging process influences the physical capacities of the elderly, making them more susceptible to falling and functional limitations. Impaired postural balance increases the risk of falls in the elderly. Virtual reality exercise has been widely used for postural balance training. Objective: this study is to investigate the effect of physical exercises with virtual reality on the body balance of the elderly. Methodology: For this systematic review, the PRISMA method was used, selecting randomized and controlled articles published until January 2021, which used video games as a resource for the rehabilitation of body balance in the elderly. The database used was PubMed. Results: 316 studies were found, after the screening phases we selected 7 studies for this systematic review. The studies underwent a methodological evaluation using the JADAD scale. The size of the intra-group effect (ESw) varied from small to very large (0.23-2.41) for the group that used VR as an intervention, while for the control group the effect size varied from trivial to large ( 0.00-1.98). However, the size of the inter-group effect varied from trivial to perfect (0.00-5.87) showing a greater effect for the use of VR. Conclusion: We conclude that the use of VR for rehabilitation of body balance is beneficial for the elderly population.